Analisis Nilai Moral dalam Cerita Jaka Tarub - Rozaqi, Achmad Fahri; Amalia, Alifah; Arifa, Arifa; Mas’odi, Mas’odi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The folklore of Jaka Tarub comes from Central Java which tells the story of a village youth named Jaka Tarub, who is known to be brave and an expert hunter who married an angel. This study aims to analyze the moral values contained in the folklore of Jaka Tarub. This story was chosen because it is one of Indonesia's traditional legends that is full of moral messages and local wisdom. The method used in this study is qualitative descriptive analysis, with a moral literary study approach. The results of the analysis show that in the story of Jaka Tarub there are several moral values about the importance of honesty, trust, and responsibility for one's own actions. This story also illustrates the consequences of excessive curiosity and lessons to value promises and trust in relationships. This story has various versions and is an important part of Javanese culture that is passed down orally and in writing. These values are conveyed through the characters in the story, the conflicts that occur, and the resolution of the story that contains life lessons. By understanding the moral values in this story, it is hoped that readers can learn lessons and apply them in their daily lives.